2015
DOI: 10.1002/bit.25568
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of altered N‐glycosylation‐related gene expression in recombinant Chinese hamster ovary cells subjected to elevated ammonium concentration by digital mRNA counting

Abstract: To understand the effects of ammonium on N-glycosylation, recombinant Chinese hamster ovary (rCHO) cells that produce the Fc-fusion protein were cultivated in serum-free suspension cultures with 10 mM ammonium addition. The addition of ammonium to the cultures reduced the relative proportion of acidic isoforms and sialic acid content of an Fc-fusion protein. Fifty two N-glycosylation-related gene expressions were assessed by the NanoString nCounter system, which provides a digital readout using custom-designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
1
31
1
Order By: Relevance
“…While the NanoString nCounter has the capacity to quantify a large subset of mRNAs belonging to varied and linked pathways, we have used the current studies to define mRNAs that are most likely to provide an informative fingerprint of cellular state. The smaller subset offers the potential for exploitation to interrogate a range of cellular challenges such as sodium butyrate treatment, hyperosmotic conditions, or elevated ammonium concentrations . Despite the profiling observed in this study, further work will be needed to refine the association between mRNA expression patterns and cellular phenotypes (and to provide deeper understanding of molecular descriptions of cellular phenotype).…”
Section: Discussionmentioning
confidence: 97%
“…While the NanoString nCounter has the capacity to quantify a large subset of mRNAs belonging to varied and linked pathways, we have used the current studies to define mRNAs that are most likely to provide an informative fingerprint of cellular state. The smaller subset offers the potential for exploitation to interrogate a range of cellular challenges such as sodium butyrate treatment, hyperosmotic conditions, or elevated ammonium concentrations . Despite the profiling observed in this study, further work will be needed to refine the association between mRNA expression patterns and cellular phenotypes (and to provide deeper understanding of molecular descriptions of cellular phenotype).…”
Section: Discussionmentioning
confidence: 97%
“…Analysis of 52 N-glycosylated gene expressions by the NanoString nCounter system, which can provide a direct digital readout using customdesigned color-coded probes, revealed that hyperosmolality, unlike ammonia (Ha et al, 2015) and NaBu treatment , did not increase sialidase-1 and sialidase-3 gene (neu1 and neu3) expression. Analysis of 52 N-glycosylated gene expressions by the NanoString nCounter system, which can provide a direct digital readout using customdesigned color-coded probes, revealed that hyperosmolality, unlike ammonia (Ha et al, 2015) and NaBu treatment , did not increase sialidase-1 and sialidase-3 gene (neu1 and neu3) expression.…”
Section: Discussionmentioning
confidence: 99%
“…The DUKX-Fc was established as described previously (Ha et al, 2015). The Fc-fusion protein is a homodimer with two glycosylation sites in the head protein and one in the Fc region of human IgG4.…”
Section: Cell Line and Culture Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, culture condition can also be optimized to reduce the expression level of glycosidases including sialidase. Recently, it was reported that sodium butyrate concentration and ammonium concentration significantly affected the expression level of sialidase …”
Section: Resultsmentioning
confidence: 99%